2012
DOI: 10.1074/jbc.m112.361865
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Clearance of α-Synuclein in Saccharomyces cerevisiae Depends More on Autophagosome and Vacuole Function Than on the Proteasome

Abstract: Background:The hallmark of Parkinson disease is ␣-synuclein aggregation, whose cytotoxic effects are reproducible in yeast. Results: ␣-Synuclein aggregate clearance is impaired by vacuolar protease inhibitor PMSF but not by proteasome inhibitor MG132. Conclusion: Yeast recovers from ␣-synuclein-induced toxicity by clearing aggregates via autophagy and vacuolar pathways. Significance: The data provide insight into the mechanisms used by yeast cells to clear toxic aggregated proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 73 publications
11
99
1
Order By: Relevance
“…8B). These results corroborate our previous findings (38). Western blot hybridization of MG132-treated cells with ubiquitin antibody confirmed the effectiveness of MG132 as a proteasome inhibitor (Fig.…”
Section: Phosphorylation Promotes Proteasome and Autophagy Degradatiosupporting
confidence: 93%
See 4 more Smart Citations
“…8B). These results corroborate our previous findings (38). Western blot hybridization of MG132-treated cells with ubiquitin antibody confirmed the effectiveness of MG132 as a proteasome inhibitor (Fig.…”
Section: Phosphorylation Promotes Proteasome and Autophagy Degradatiosupporting
confidence: 93%
“…We previously showed that expression of WT ␣Syn from two copies is under the threshold for yeast growth inhibition (38). Thus, yeast smt3 ts strains expressing WT ␣Syn from two genomically integrated gene copies were constructed, and the number of integrated copies was verified by Southern hybridization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations